2019
DOI: 10.1186/s12870-018-1576-y
|View full text |Cite|
|
Sign up to set email alerts
|

SNP genotyping elucidates the genetic diversity of Magna Graecia grapevine germplasm and its historical origin and dissemination

Abstract: BackgroundMagna Graecia is the ancient name for the modern geopolitical region of South Italy extensively populated by Greek colonizers, shown by archeological and historical evidence to be the oldest wine growing region of Italy, crucial for the spread of specialized viticulture around Mediterranean shores. Here, the genetic diversity of Magna Graecia grape germplasm was assessed and its role in grapevine propagation around the Mediterranean basin was underlined.ResultsA large collection of grapevines from Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 64 publications
(123 reference statements)
10
68
1
Order By: Relevance
“…Apulia, stretching into the Mediterranean Sea, has a strategic geographical position, being located on commercial routes of ancient populations such as Phoenicians, Greeks, and Romans. A recent study remarked the central role of Magna Graecia in the spread of grapevine to Western Europe, corroborating the hypothesis that grapevine originated in the Caucasus and then spread to the regions of Southern Italy [39].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Apulia, stretching into the Mediterranean Sea, has a strategic geographical position, being located on commercial routes of ancient populations such as Phoenicians, Greeks, and Romans. A recent study remarked the central role of Magna Graecia in the spread of grapevine to Western Europe, corroborating the hypothesis that grapevine originated in the Caucasus and then spread to the regions of Southern Italy [39].…”
Section: Discussionsupporting
confidence: 58%
“…The history of the Mediterranean settlement, trade, and cultural influence supports this hypothesis. Greeks colonized the southern area of Apulia, and evidence of gene flow between Greece and Apulia has been observed [39]. Conversely, there is minor evidence of gene flow in the Gargano, due to a tardive colonization by the Greeks (from the end of V century B.C.).…”
Section: High Throughput Snp Genotyping Reveals Patterns Of Genetic Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, varieties bearing chlorotypes B, C, and D, found more frequently in Eastern wine varieties (B and D) and table grape varieties (C) (Arroyo-García et al, 2006;Laucou et al, 2018) were also found in Portuguese varieties (Cunha et al, 2009;Cunha et al, 2010;Castro et al, 2013;Cunha et al, 2015) supporting their multiple origins, likely including introductions from the Near East and from the Maghreb. Secondary domestication events have been proposed for grapevine along the Mediterranean basin based on differences in chlorotype frequencies (Grassi et al, 2003;Arroyo-García et al, 2006) or on the increased expected heterozygosity values detected further from the putative center of origin of the species (De Lorenzis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The SNP markers have been used to evaluate diversity within many species, such as Populus trichocarpa [31], Vitis vinifera [32], Ginkgo biloba [33]. SNPs called from transcriptome sequencing is a more efficient strategy for characterizing diversity in non-model or massive-genome species, since the sequences are detected on the coding regions rather than the whole genome.…”
Section: Discussionmentioning
confidence: 99%